Children's Naive Concepts of OCD and How They Are Affected by Biomedical Versus Cognitive Behavioural Psychoeducation - Wilson, Charlotte; Butlin, Ben (My University, 2018)
Background: How we conceptualize mental health conditions is important as it impacts on a wide range of mediators of treatment outcome. We do not know how children intuitively conceptualize obsessive-compulsive disorder (OCD), nor do we know the relative impact of biomedical or cognitive behavioural conceptual explanations, yet both are being widely used in psychoeducation for children with OCD. Aims: This study identified children's naive concepts of OCD, and the comparative impact of biomedical versus cognitive behavioural psychoeducation on perceived prognosis. Method: A within- and between-subjects experimental design was used. After watching a video of a young person describing their OCD, 202 children completed a questionnaire examining their concepts of the condition. They repeated the questionnaire following a second equivalent video, this time preceded by either biomedical or cognitive behavioural psychoeducation. Results: Participants’ naive concepts of OCD reflected predominant models of OCD in healthcare. Even at the minimal dose of psychoeducation, participants’ conceptualizations of OCD changed. Prior exposure to OCD resulted in a stronger alignment with the biomedical model. Exposure to biomedical psychoeducation resulted in participants predicting a slower recovery with less chance of complete remission. Conclusion: Psychoeducation for childhood OCD is impactful. Despite its wide use by clinicians and mental health services, biomedical psychoeducation appears to have deleterious effects. Children's concepts of OCD merit attention but caution should be applied in how they are targeted.
PUBLISHED
Keywords: Children; Adolescents; Obsessive-compulsive disorder; Causal attributions; CBT; Identities in Transformation; OCD; PSYCHOEDUCATION